The Influence of Processing Parameters on the Tensile Strength of 3D Printed Products - Trinh, Van-Long; Hoang, Tien-Dung; Ngo, Quang-Tu (Engineering, Technology & Applied Science Research, 2025)
Additive Manufacturing (AM) is a modern method of producing parts by depositing material layers on each other. The technology can be used to fabricate many different types of products for daily applications. Tensile Strength (TS) is one of the most important mechanical properties of fabricated products, such as 3D-printed products. This study investigates the influence of Additive Manufacturing Parameters (AMPs) on the TS of manufactured products. 3D printed samples were produced using Fused Deposition Modeling (FDM) technology with Polylactic Acid (PLA) material. The AMPs investigated were temperature, speed, layer thickness, and bed temperature. TS tests were carried out on a tensile testing machine, and the results showed that AMPs have a great influence on TS. In addition, the optimal set of AMPs was found for the manufacturing process to improve TS. TS can be predicted using a response model obtained from response optimization analysis. The results of this study can be applied in various practical applications.